5-Chloroindoline-2,3-dione - Wen-Bin Wei; Shuo Tian; Hao Zhou; Jie Sun; Hai-Bo Wang (Acta Crystallographica Section E, 2010)
The title compound, C8H4ClNO2, is almost planar (r.m.s. deviation for the non-H atoms = 0.023 Å). In the crystal, N—H...O hydrogen bonds link the molecules into C(4) chains propagating in [001] and C—H...O interactions cross-link the chains.